Improving Listening Skills to English as a Second Language Learners - Fazilat Abdurahmonovna Musayeva (Web of Journals Publishing, 2023)
This article indicates what problems students of a foreign language as a second language encounter most during their studies and the reasons for this. It was noted that listening, which is considered the main element of language skills, is useful for students in the process of speaking. Tips and techniques for improving listening comprehension skills for people with English as a second language were also discussed.
Keywords: language skills, ESL, cognitive strategies, listening practice, pre-listening activities, while–listening activities, post-listening activities, video tools.